2020
DOI: 10.1152/ajpregu.00243.2019
|View full text |Cite
|
Sign up to set email alerts
|

Low-load resistance training to task failure with and without blood flow restriction: muscular functional and structural adaptations

Abstract: The application of blood flow restriction (BFR) during resistance exercise is increasingly recognized for its ability to improve rehabilitation and for its effectiveness in increasing muscle hypertrophy and strength among healthy populations. However, direct comparison of the skeletal muscle adaptations to low-load resistance exercise (LL-RE) and low-load BFR resistance exercise (LL-BFR) performed to task failure is lacking. Using a within-subject design, we examined whole muscle group and skeletal muscle adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 60 publications
3
54
2
5
Order By: Relevance
“…For that matter, a current research comparing BFR training and LLT over 6 weeks, showed the volume of the training to be 33% lower and results favorable to BFR group, but without any statistically significant value. 35 The American Academy of Orthopedic Surgeons -AAOS, the Osteoarthritis Research Society International -OARSI, and the American College of Rheumatology explain that strength increment promotes pain reduction, in addition to attenuating symptomatology, reducing joint damage progress [36][37][38] on individuals with knee osteoarthritis. It was observed that all osteoarthritis patients interventions are due to neural activation and increased quadriceps strength, since these subjects have decreased this musculature strength due to arthrogenic muscle inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…For that matter, a current research comparing BFR training and LLT over 6 weeks, showed the volume of the training to be 33% lower and results favorable to BFR group, but without any statistically significant value. 35 The American Academy of Orthopedic Surgeons -AAOS, the Osteoarthritis Research Society International -OARSI, and the American College of Rheumatology explain that strength increment promotes pain reduction, in addition to attenuating symptomatology, reducing joint damage progress [36][37][38] on individuals with knee osteoarthritis. It was observed that all osteoarthritis patients interventions are due to neural activation and increased quadriceps strength, since these subjects have decreased this musculature strength due to arthrogenic muscle inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the authors observed a significant increase in citrate synthase activity and state 3 respiration rates in normoxic resistance training environment, which again suggests that resistance training in lieu of hypoxia may not stimulate appreciable mitochondrial adaptations. Others have also investigated the effects of low-load resistance training (with or without blood flow restriction) to failure for six weeks in a within-subject design [66]. Both legs had similar muscle strength and size increases.…”
Section: Mitochondrial Adaptations To Resistance Training In Youngermentioning
confidence: 99%
“…To our knowledge, this will be the first intervention study to investigate BFR-RT in this population. Considering that current evidence shows BFR-RT is a safe method, even for frail populations [15,17,18], we believe BFR-RT will result in important increases in muscle mass and strength, accompanied by increases in functionality, with no negative outcomes on cirrhosis condition. There are some limitations to this study.…”
Section: Discussionmentioning
confidence: 88%
“…In this sense, evidence shows that low-load RT combined with partial blood flow restriction (BFR-RT) results in significant muscle mass gains, comparable to high-load RT [15,16] or low-load RT to muscle failure [17]. Its applicability in frail populations (e.g., elderly and cardiac patients) also has been verified, with positive outcomes after the intervention period [15,18,19], including functional performance [20].…”
Section: Introductionmentioning
confidence: 98%